A class of nonlinear systems with new boundary conditions: existence of solutions, stability and travelling waves - Lamamri, Abdelkader; Gouari, Yazid; Dahmani, Zoubir; Rakah, Mahdi; Sarıkaya, Mehmet Zeki (Mathematical Modelling and Analysis, 2025)
In this work, we begin by introducing a new notion of coupled closed fractional boundary conditions to study a class of nonlinear sequential systems of Caputo fractional differential equations. The existence and uniqueness of solutions for the class of systems is proved by applying Banach contraction principle. The existence of at least one solution is then accomplished by applying Schauder fixed point theorem. The Ulam Hyers stability, with a limiting-case example, is also discussed. In a second part of our work, we use the tanh method to obtain a new travelling wave solution for the coupled system of Burgers using time and space Khalil derivatives. By bridging these two aspects, we aim to present an understanding of the system’s behaviour.